Impact of Supply Chain Integration, Supply Chain Responsiveness, and Innovation Capability on Operational Performance in Era Covid-19 - Hotlan Siagian; Dillwyn Felix Johono (Petra International Journal of Business Studies, 2022)
The study investigated the influence of supply chain integration on operational performance through supply chain responsiveness and innovation capability. Data collection used a questionnaire designed with a 7-point Likert scale in Google Form and printed format. The questionnaire is distributed through social media, email, WhatsApp, and mail posts. The sampling method uses probability sampling technique utilizing online software https://numbergenerator.org/. Of the 266 population of food and beverage companies in East Java, as many as 140 samples were selected. Data analysis used the partial least square technique (PLS) utilizing SmarrtPLS Version 3.0 software. The analysis results showed that the nine hypotheses formulated were empirically and significantly supported. Supply chain integration affects supply chain responsiveness, innovation capability, and operational performance. In addition, supply chain responsiveness and innovation capability positively affect operational performance. This study's exciting and new findings are the mediating role of supply chain responsiveness and innovation capability. This result offers solutions to practitioners to build supply chain integration, supply chain responsiveness, and innovation capability to improve operational performance. The theoretical contribution of this research is mainly in the mediating role of supply chain responsiveness and innovation capability on the influence of supply chain integration on operational performance.